Gut microbiome characteristics of women with hypothyroidism during early pregnancy detected by 16S rRNA amplicon sequencing and shotgun metagenomic - Hu, Lin; Li, Jingjing; Zhang, Miao; Sun, Zongzong; Ban, Yanjie; Tian, Xin; Liu, Dong; Hu, Lulu (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThis study aimed to explore the correlation between microbiota dysbiosis and hypothyroidism in early pregnancy by 16S rRNA amplicon sequencing combined with metagenomic sequencing.MethodsSixty pregnant women (30 with hypothyroidism and 30 normal controls) were recruited for 16S rRNA amplicon sequencing, and 6 patients from each group were randomly selected for metagenomic sequencing to assess the gut microbiome profile.ResultsThe 16S rRNA results showed that beta-diversity in the hypothyroidism group was decreased. The relative abundances of the Prevotella and Paraprevotella genera increased in the hypothyroidism group, and Blautia predominated in the controls. The metagenomics results revealed that Prevotella_stercorea_CAG_629, Prevotella_hominis, Prevotella_sp_AM34_19LB, etc. were enriched in the hypothyroidism group at the species level. Functional analysis revealed that the pyridoxal 5’-phosphate synthase pdxT subunit module was decreased, and the short-chain fatty acid (SCFA) transporter and phospholipase/carboxylesterase modules were strongly enriched in the hypothyroidism group. Hypothyroidism patients had increased C-reactive protein (CRP), interleukin-2 (IL-2), IL-4, IL-10, and tumor necrosis factor (TNF)-α levels. The pyridoxal 5’-phosphate synthase pdxT subunit, the SCFA transporter, and the phospholipase/carboxylesterase module were associated with different Prevotella species.ConclusionIn early pregnancy, women with hypothyroidism exhibit microbiota dysbiosis, and Prevotella may affect the metabolism of glutamate, SCFA, and phospholipases, which could be involved in the development of hypothyroidism during pregnancy.